Reductions in Postprandial Plasma Allantoin Concentrations With Increasing Doses of Polyphenol Rich Curry Intake – A Randomized Crossover Trial - Haldar, Sumanto; Pakkiri, Leroy Sivappiragasam; Lim, Joseph; Chia, Siok Ching; Ponnalagu, Shalini; Drum, Chester Lee; Henry, Christiani Jeyakumar (Frontiers in Physiology, 2019)
While dietary or supplementary antioxidants are thought to inhibit or delay oxidation of biological molecules, their utility in vivo has been marred by equivocal evidence. Consumption of polyphenol rich foods has been previously shown to alleviate postprandial oxidative stress and/or improve endothelial function. Although, previous studies suggested the utility of allantoin as a biomarker of oxidative stress, controlled dose response studies with dietary antioxidants to test this in humans have been limited. We therefore investigated the effects of 2 doses of polyphenol rich curry consumption on postprandial plasma concentrations of allantoin, allantoin to uric acid ratio, F2-isoprostanes using liquid chromatography-tandem mass spectrometry (LCMS-MS) and measured endothelial function using peripheral arterial tonometry (endoPAT). In a randomized controlled crossover trial in 17 non-smoking, healthy, Chinese men, aged 23.7±2.4 years and BMI 23.1±2.3 kg/m2, the volunteers consumed 3 test meals in a random order, consisting of either non-curry Dose 0 Control (D0C, 0 g spices), or Dose 1 Curry (D1C, 6 g spices) or Dose 2 Curry (D2C, 12 g spices), after overnight fast. There were significant reductions in postprandial allantoin concentrations (p<0.001) and allantoin to uric acid ratio (p<0.001) at 2 h and 3 h following test meal consumption, indicating improvements in postprandial redox balance with increasing curry doses, although there were no differences between treatments on F2-isoprostane concentrations or on RHI (measured at 2 h only). Allantoin may have a utility as a biomarker of redox balance, in an acute setting. The study was registered at www.clinicaltrials.gov (Identifier No. NCT02599272).